FRI0606 Characteristics and treatment of new onset arthritis after checkpoint inhibitor therapy. (15th June 2017) - Christ, LA; Mönch, S; Hasmann, S; Goldscheider, I; Heppt, M; Berking, C; Berger, F; Dechant, C; Skapenko, A; Schulze-Koops, H; Leipe, J
Abstract : Background: The recent introduction of biologic agents targeting immunologic checkpoints (immunologic checkpoint inhibitors (ICI)) established immunotherapy as a highly effective cancer therapy. ICI that trigger an anti-tumor response by activation of T cells, may also cause immune-related adverse events (irAEs). Characterization of rheumatic adverse events such as arthritis and data on treatment of irAEs are scarce. Objectives: To characterize patients with new-onset arthritis under ICI therapy and to assess the efficacy and safety of treatment that aimed to balance anti-tumor and anti-inflammatory therapy. Methods: In this prospective observational study, patients with melanoma receiving ICI therapy who experienced arthralgias were evaluated for the presence of musculoskeletal inflammation. Data on demographics, ICI regime, time of onset and response to therapy of musculoskeletal irAEs, imaging, joint count, CRP/ESR, and immune serology were collected. Further, response to anti-inflammatory therapies including NSAR, glucocorticoids (GC) and methotrexate was assessed. Results: Of 7 patients with arthralgias after initiation of ICI therapy, all had objective signs of musculoskeletal inflammation. Arthritis was demonstrated in 6 patients, 3 oligoarthritis (SpA pattern), 2 polyarthritis (RA pattern), 1 monoarthritis. PMR-like disease with typical ultrasound findings was evident in 1 case. The time from start of ICI therapy to onset of synovitis symptoms varied from 1 to 259 days without a timely association to other irAEs. Upon first visit in our clinic, CRP levels were elevated in 6 of the patients (5.5 to 107 mg/l) while immune serology was positive only in one patient (high titer RF and ACPA). Interestingly, in this patient low RF and ACPA titers had been detected when she presented with arthralgias without synovitis five years prior. This patient developed highly active RA one day after the first infusion of nivolumab. Retrospective analysis of cancer staging imaging studies revealed good sensitivity for PET-CT in the detection of synovitis, as opposed to contrast-enhanced CT. The baseline mean overall disease burden (assessed by VAS for pain, 0–10) was 7.6±0.8 and was significantly reduced after 3 months of anti-inflammatory treatment to 1±1.4. Initially, all patients were treated with systemic and four patients also with intraarticular GC. Four of 7 patients flared on GC treatment upon tapering and were given methotrexate. Remission was achieved in all and prednisolone could be tapered. Patients were followed for a median of 152 days, and no safety signal with regard to tumor reappearance was detected. Conclusions: All patients with arthralgias upon ICI therapy had arthritis or PMR-like disease suggesting a need for increased awareness for musculoskeletal irAE. Inflammatory manifestations were associated with high disease burden and not self-limiting. While GC therapy is effective, flares were frequent after tapering and, thus, potential side-effects including attenuation of the anti-tumor efficacy of ICI are a concern. This is the first report on the efficacy and safety of methotrexate as a GC-sparing agent in ICI-induced arthritis. Disclosure of Interest: None declared